Odpowiedzi

2010-01-10T12:24:36+01:00
X-2y+3=3x-3y+5
6x+5y+1=y-2x

y=2+2x
8x+4(2+2x)=-1

y=2+2x
8x+8+8x=-1

y=2+2x
16x=-9 /:16

x=-9/16
y=2+2*9/16

x=-9/16
y=7/8
2010-01-10T12:24:47+01:00
X - 2y + 3 = 3x - 3y + 5
6x + 5y + 1 = y - 2x

-2x + y = 2 I × (-4)
8x + 4y = -1

8x - 4y = -8
8x + 4y = -1
.................... [dodajemy układ]

16x = -9 I : 16
8x + 4y = -1

x = -9/16
-4 1/2 + 4y = -1

x = -9/16
4y = 3 1/2 I :4

x = -9/16
y = 7/8
Najlepsza Odpowiedź!
2010-01-10T12:29:00+01:00

x - 2y + 3 = 3x - 3y + 5
6x + 5y + 1 = y - 2x
Metoda przeciwnych współczynników

-2x + y = 2 I × (-4)
8x + 4y = -1

8x - 4y = -8
8x + 4y = -1

16x = -9 / : 16
8x + 4y = -1

x = -9/16
-4 1/2 + 4y = -1

x = -9/16
4y = 3 1/2 / :4

x = -9/16
y = 7/8